INVENTARISASI MAKROINVERTEBRATA BENTIK DI SUNGAI MENTUKA KABUPATEN SEKADAU KALIMANTAN BARAT - Sangau, Paulus; Junardi, Junardi; Rousdy, Diah Wulandari (Universitas Tanjungpura, 2019)
The existence of Ephemeroptera, Plecoptera and Trichoptera (EPT) macroinvertebrates in water can be used as the indicators to identify the water quality. This study aims to determine the diversity of Macroinvertebrates and physical and chemical factors in water of the Mentuka River. Macroinvertebrate sampling was carried out in February 2018 using random with surber and dip net at three stations spread overthe upstream, middle and downstream of the Mentuka River. The measurements chemicals and physical factors such as water temperature, brightness, current velocity, depth, TDS, TSS, acidity (pH), dissolved oxygen (DO) and free carbon dioxide (CO2), which is carried out together with macroinvertebrates sampling. There are 378 macroinvertebrates individuals belonging to nine genera, namely Polypedilum, Hydropsyche,Â Anthopotamus, Baetis, Acroneuria, Libellula, Rhyacophila, Parathelphusa and Macrobrachium in Mentuka River. The Ephemeroptera, Baetis is the most abundance with 5.76 ind/m2. Based on the diversity index, the Mentuka was categorized as moderately polluted river.